LIFETIME ESTROGEN EXPOSURE IS ASSOCIATED WITH COGNITIVE STATUS IN LATE LIFE: THE CACHE COUNTY STUDY - Matyi, J (Innov Aging, 2018)
The use of the exogenous hormone estrogen has been associated with cognitive outcomes in late life. We examined the relationship between lifetime estrogen exposure and cognitive decline in older female participants of a 12-year population-based study. 2114 women (mean age = 74.94 years, SD = 6.71) who were dementia-free at baseline completed a women’s health questionnaire, including questions regarding reproductive history and hormone-replacement therapy (HRT). Endogenous estrogen exposure (EEE) was calculated as the duration between age at menarche to age at menopause, adjusting for pregnancy and breastfeeding. HRT variables included duration of use, type (unopposed; opposed), and HRT initiation timing. The Modified Mini-Mental State Examination (3MS) was administered approximately 3 – 4 years apart (up to 4 times) to broadly assess cognitive status. Linear mixed-effects models examined the relationship between lifetime estrogen exposure and 3MS score over time. EEE was positively associated with cognitive status (though not decline) at trend-level significance (β = 0.03, p = .054). Additionally, longer duration of HRT use was positively associated with cognitive status (β = 0.02, p = .046) with an age interaction, such that older women had greater benefit compared to younger women. Timing of HRT initiation was significantly associated with 3MS (β = 0.55, p = .048), with higher scores for women initiating HRT within 5 years of menopause compared to those initiating 6 or more years later. Overall, these results suggest longer EEE and HRT use, especially in older women, are beneficial for cognitive status in late life.